(3CfSGH SjO GdeQSdjf hMHjH QH GdYGdejfs - (3GdbGSej, GdOGQj, eMeO Hf CMeOs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfgPg JMaI TQjaI hXQa efjaI JNJUQ HGdefUH GdeWgQ GdfHhj hGdaNQ GdebOSj GdeMeOjs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQghNGdag aj GdLGgdjI abjd Efg GdebOGO Hf GdCShO hbjd dg GdcfOj dCf CHG YeQh Hf HWdg cGfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3aj Chdg Jedc HGSe eMeO eQGO GdMeQGhj SfI (B1126(3g`s
Keywords: (3GdJGQjNs